Suicide risk among veterans using VHA justice-involved services: a latent class analysis - Ryan Holliday; Adam R. Kinney; Alexandra A. Smith; Jeri E. Forster; Matthew A. Stimmel; Sean C. Clark; Shawn Liu; Lindsey L. Monteith; Lisa A. Brenner (BMC Psychiatry, 2023)
Abstract Background Justice-involved Veterans experience notable risk for psychosocial stressors (e.g., homelessness) and psychiatric multimorbidity, which can result in complex clinical presentations. However, research examining how such factors coalesce to impact risk for suicide remains limited. Methods We conducted a latent class analysis of 180,454 Veterans accessing Veterans Health Administration (VHA) justice-related services from 2005 to 2018. Results A four-model class membership solution was identified. Among these classes, risk for suicide was highest among Veterans with greater psychiatric burden, with risk most notable among those with high VA service use. Veterans seeking healthcare primarily focused on substance use disorders or with low psychiatric burden and service use had a lower risk for suicide. Conclusions Psychiatric multimorbidity is salient as it relates to suicide among Veterans accessing VHA justice-related services. Further evaluation of existing VHA services for this population and methods of augmenting and enhancing care for justice-involved Veterans with histories of co-occurring psychiatric conditions may be beneficial in facilitating suicide prevention efforts.